Cascelli, Antonio and Denis Condon, eds. Experiencing Music and Visual Cultures: Threshold, Intermediality, Synchresis. London and New York: Routledge, 2021 [ISBN: 978-0-367-18804-7] - Merino Martínez, Aitor (Eikón / Imago, 2024)
Book review of Experiencing Music and Visual Cultures: Threshold, Intermediality, Synchresis, edited by Cascelli, Antonio and Denis Condon. London and New York: Routledge, 2021 [ISBN: 978-0-367-18804-7].